Hemicellulose-g-PAAc/TiO2 Nanocomposite Hydrogel for Dye Removal - Li, Yudan; Sun, Xiao-Feng; Chen, Jiayi; Sun, Le (Journal of Research Updates in Polymer Science, 2023)
Dyes pollution on urban environment is of great concern because of the human health hazards associated with this kind of contaminants, and the use of low-cost photocatalytic composite material is an efficient treatment method to minimize the environmental impact. A novel hemicellulose-g-PAAc/TiO2 composite hydrogel was prepared as a promising alternative material for dye removal. Wheat straw hemicellulose and TiO2 nanoparticles were first modified and then incorporated into hydrogel via covalent bonds. Effects of gel dosage, pH, initial concentration and contact time on the adsorption amount of methylene blue were systematically studied using the prepared hydrogel. The equilibrium adsorption data was fitted well to the Freundlich isotherm model, and Langmuir isotherm analysis indicated that the adsorption capacity of the hemicellulose-g-PAAc/TiO2 composite hydrogel was 389.1 mg/g, and adsorption kinetic study showed that the adsorption process can be described by the pseudo second-order kinetic model. The prepared composite hydrogel exhibited high photodegradation ability for methylene blue under alkaline conditions, and all results indicated that the hemicellulose-g-PAAc/TiO2 composite hydrogel had excellent photocatalytic degradability for dyes, which can be used in practical process.